The effect of employee work related attitudes on employee job performance: a study of non academic staff (skilled labors) of the university of jaffna - Malini, G.; Atchyuthan, N. (University of Jaffna, 2016)
Work related attitudes are the feelings employees have toward different aspects of the work environment. Job satisfaction, job involvement and organizational commitment are three key attitudes that are the most relevant to important outcomes. When people have more positive work attitudes, they may have the inclination to perform better. Thus to sustain within the competition and to achieve the competitive advantage, it is vital to focus on the attitudes and respective job performance of the employees in a significant manner. This study reveals how employee work related attitudes impact on non- academic staffs' (Skilled labors) performance of University of Jaffna. Therefore the objective of this study is to find out the relationship between employee work related attitudes and employee job performance. For the purpose of this study, data collection was done through the questionnaire and reliability of the items was confirmed. Further, 88 respondents were selected based on convenient sampling method from non-academic staffs (Skilled labors) in University of Jaffna. SPSS was used to analyze the data and statistical tools such as correlation and regression were applied to measure the relationship between variables. This is the first study to investigate the relationship between employee work related attitudes and employee performance of non academic staffs (Skilled labors) in University of Jaffna. The finding indicated that there is a significant relationship between employee works related attitudes and employee job performance.
Keywords: Employee job performance; Job satisfaction; Job involvement; Organizational commitment; Work related attitudes